Effect of fibre aspect ratio on the torsional behaviour of steel fibre-reinforced normal weight concrete and lightweight concrete - Yap, Soon Poh; Khaw, K.R.; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin (Elsevier, 2015)
The emergence of torsion studies is attributed to the increasing demand for the aesthetic design of curved structural members; however, they are limited in respect of lightweight concrete. Oil Palm Shell Concrete (OPSC) has been researched in Malaysia, which is known to produce a sustainable lightweight concrete by using locally available oil palm shell waste. This study aims to compare the torsional behaviour between the normal weight concrete (NWC) and OPSC, and to investigate the effects of steel fibre of varying aspect ratio - 55, 65 and 80 - in both types of concrete. The results showed that OPSC is more ductile in torsion than the NWC beam, with a twist at failure 2.8 times that of NWC. The steel fibre reinforcement compensated the weak tensile strength of OPSC and enhanced the mechanical properties, torsional strength and ductility, toughness and crack resistance of the OPSFRC specimens. The effect of the aspect ratio is evident from the OPSFRC-80 mix reinforced with steel fibre of aspect ratio 80, which produced the highest ultimate torque, twist at failure and torsional toughness of 8.60. kN. m, 0.179. rad/m and 1.074. kN. m/m, respectively. In addition, equations are proposed to predict the cracking and ultimate torques to improve the torsion design of lightweight concrete.